Dark continent : Europe's twentieth century - Mazower, Mark, 1958- (New York : Vintage Books ; Distributed by Random House, 2000)
Instead of seeing Europe as the natural home of freedom and democracy, Mazower argues that it was a frequently nightmarish laboratory for social and political engineering, inventing and reinventing itself through war, revolution and ideological competition. Fascism and communism should be regarded not as exceptions to the general rule of democracy, but as alternative forms of government that attracted many Europeans by offering different solutions to the challenges of the modern world. By 1940 the prospects for democratic government looked bleak, and Europe's future seemed to lie in Hitler's hands. Yet freedom was given another chance with the defeat of the Nazi New Order, and it prevailed decades later across the continent with the collapse of the Iron Curtain.
Mazower's extraordinarily skilled and insightful analysis provides us with a new perspective on the events of the century. From the beginnings of the First World War to the establishment of the European Union, he depicts a battle for hearts and minds that reached more deeply than ever before into the daily lives of ordinary people. Vividly written and vigorously argued, Dark Continent presents both a comprehensive history of twentieth-century Europe and a provocative vision of its future.--from the publisher
Includes bibliographical references (p. 417-449) and index.
Keywords: Europe -- History -- 20th century